The variety of local religious life in the Near East in the Hellenistic and Roman periods - Kaizer, Ted. (Religions in the Graeco-Roman World, 2008)
A 'Near Eastern religion', along the lines of 'Greek religion' or 'Roman religion', is hard to distinguish for the Classical period, since the religious cultures of the many cities, villages and regions that constituted the Near East in the Hellenistic and Roman periods were, despite some obvious similarities, above all very different from each other. This collection of articles by scholars from different disciplines (Ancient History, Archaeology, Art-History, Epigraphy, Numismatics, Oriental Studies, Theology) contributes to our quest for understanding the polytheistic cults of the Near East as a whole by bringing out the variety between the different local and regional forms of worship in this part of the world.